Childhood Stature and Growth in Relation to First Ischemic Stroke or Intracerebral Hemorrhage. Issue 3 (March 2018) - Gjærde, Line Klingen; Truelsen, Thomas Clement; Baker, Jennifer Lyn
Abstract : Background and Purpose—: Attained height, an indicator of genetic potential and childhood growth environment, is inversely associated with stroke, but the mechanisms are poorly understood. We investigated whether childhood height and growth are associated with ischemic stroke (IS) and intracerebral hemorrhage (ICH). Methods—: In a cohort of Danish schoolchildren born 1930 to 1989, with measured height from 7 to 13 years, we investigated associations of childhood stature and growth with risks of adult IS and ICH. Cox proportional hazards regressions were performed to estimate hazard ratios (HRs) with CIs separately for women and men. Results—: Among 311 009 individuals, 10 412 were diagnosed with IS and 2546 with ICH. Height at 7 years was inversely and significantly associated with IS in both sexes (per z score, equivalent to ≈5.2 cm in women and 5.1 cm in men; women: HR=0.89 [95% CI: 0.87–0.92]; men: HR=0.90 [95% CI: 0.88–0.92]) and with ICH in men (HR=0.89 [95% CI: 0.84–0.94]) but not in women (HR=0.97 [95% CI: 0.91–1.04]). Associations were similar at older childhood ages and were stable throughout the study period. No statistically significant associations for growth from 7 to 13 years were observed for IS or ICH. Conclusions—: Short stature at 7 to 13 years is significantly associated with increased risks of IS in both sexes and with ICH in men. Growth during this period of childhood is not significantly associated with either of these stroke subtypes, suggesting that underlying mechanisms linking height with risks of stroke may exert their influence already by early childhood. Abstract : Supplemental Digital Content is available in the text.